ChemInform Abstract: Nickel‐Promoted Highly Regioselective Carboxylation of Aryl Ynol Ether and Its Application to the Synthesis of Chiral β‐Aryloxypropionic Acid Derivatives. Issue 47 (November 2015) - Saito, Nozomi; Sun, Zhongdong; Sato, Yoshihiro
Abstract: A new method for the enantioselective synthesis of the optically active title propionic acid derivatives involving the synthesis of α‐substituted‐β‐aryloxyacrylic acid derivatives from aryl ynol ether and CO2 followed by the rhodium‐catalyzed asymmetric hydrogenation is developed.